Development and pilot testing of a nurse-led common-sense model of self-regulation-based heart failure self-care program - Zehao Huang; Sek Ying Chair (BMC Nursing)
Abstract Background Self-care practices among people with heart failure (HF) remain suboptimal. Nurse-led self-care interventions hold promise in managing this condition. The Common-Sense Model (CSM) of Self-Regulation is a widely adopted theoretical framework that promotes behavior change and improves disease prognosis among patients. Therefore, this study aimed to describe the development and pilot testing of a nurse-led CSM of Self-Regulation-based self-care intervention among people with HF. Methods Intervention development was informed by a comprehensive review of the relevant literature, the CSM of self-regulation, international and national guidelines, and findings from our previous systematic reviews. The pilot study utilized a single-blinded, two-arm, parallel group, randomized controlled trial (RCT) design, adhering to the CONSORT Statement. Eligible participants were randomly assigned at a 1:1 ratio to either the intervention group or the control group. Data were collected at baseline and immediately after the intervention, with a focus on evaluating feasibility, acceptability, and potential effects. Results We developed and validated a nurse-led, theory-driven, evidence-based, and need-oriented HF self-care program. A total of 26 participants were enrolled in the pilot study, achieving an eligibility of 79.4%, a recruitment rate of 96.3%, and a retention rate of 92.3%. Most participants (83.3%) recognized the benefits of the intervention. The intervention significantly improved illness perceptions, self-care self-efficacy, and self-care behaviors among people with HF. Conclusion The nurse-led CSM of Self-Regulation-based self-care intervention is feasible, acceptable, and potentially beneficial for people with HF. A full-scale mixed-method RCT is recommended to further examine the intervention’s effectiveness. Trial registration Chinese Clinical Trial Registry (No., ChiCTR2300068156; February 9, 2023).